THE CAMBRIDGE INTRODUCTION TO INTERCULTURAL COMMUNICATION: BY GUIDO RINGS & SEBASTIAN M. RASINGER, CAMBRIDGE UNIVERSITY PRESS, 2023 - Tallone, Laura (2023)
Review of the recently published volume The Cambridge Introduction to Intercultural Communication, by Guido Rings & Sebastian M. Rasinger, Cambridge University Press, 2023